OPTIMALISASI PENGGUNAAN LAHAN PEKARANGAN DENGAN SISTEM AGROFORESTRI DI KOTA PRABUMULIH - Lensari, Delfy; Rosianty, Yuli; Syachroni, Sasua Hustati; Paridawati, Ika (Jurnal Agro Dedikasi Masyarakat (JADM), 2022)
Agroforestry is an alternative form of land use consisting of a mixture of trees with seasonal crops and or livestock in one plot of land. House yard  is one of the examples of an agroforestry system. Yards with agroforestry systems provide significant benefits that are important for the community both from the ecological and environmental, economic, and socio-cultural aspects. The purpose of this devotion is to provide knowledge to Creative KWT members to optimize home gardens with agroforestry systems (combining agricultural crops with crops forestry (timber or fruit). This devotion activity was carried out in collaboration with KKN students group 4 batch 57 Muhammadiyah University Palembang on the 9th February 2022. The location of this Community Service Activity is the Women Farmers Group (KWT) Creative Tanjung Raman Village, South Prabumulih District, Prabumulih City, Sumatra Province South. The method used in implementing the activity is conducting counseling, distributing seeds fruits, and planting and caring for fruit seedlings at KWT Kreatif. The results of this devotion can help women farmer groups to optimize the yard of the house with an agroforestry system to make it more useful for environmental ecology and the community economy. So that it can help in household economic income and while at the same time protecting and preserving the environment.